(untitled) (Journal of Educational Sciences, 2016)
The paper discusses the role of reflection in mentoring teachers at schools. The core of developing reflective abilities refers to the idea of continuing professional development of teachers entailing principles of percent-centered approaches to learning. These days, mentors and teacher educators are developing a mentoring system which facilitates novice teachers’ reflective thinking, helping them to master research skills to project one’s own strategies for selfdevelopment and professional learning. Pedagogical reflection ability of critical thinking about their professional-pedagogical activity and find constructive ways of solving pedagogical problems in terms of the number of questions and uncertainty with regard to the cognitive needs of the students. Pedagogical reflection novice teachers should be formed on the following stages of their professional development: the reflexive analysis of their leading ideas as teachers, reflective analysis of their subject knowledge to transform them into subject-pedagogical taking into account the features of the student and reflective analysis of pedagogical interaction with the school children. The Concept of 12-year General secondary education in the Republic of Kazakhstan, reflects the need for a teacher ownership meta-cognitive skills: «the ability to effectively plan, organize their educational activities, master the ways of the analysis and reflection of its activities on the development of knowledge based on the requirements of the appropriate functional literacy. Teacher-mentor responsible for the stimulation of reflexive thinking novice teacher during observations at the lesson, acting as facilitator of the whole professional activity of a teacher. During the school mentoring for us, it was essential to have appropriate methodological abilities and learning resources. In the process of mentoring is one of the most widely used methods is the «reflective conversation. Under reflective conversation we understand the problemoriented analysis of the many facts of pedagogical practice novice teachers with the help of a mentor.